PENGARUH PEMBERIAN SLUDGE INDUSTRI PENYAMAKAN KULIT TERHADAP PERKEMBANGAN TANAMAN PUCUK MERAH (SYZYGIUM OLEANA) - Dorti Jouba Nababan; Munawar Ali (EnviroUS, 2021)
The high nutrient content in the leather tanning industry sludge is the basis for exploiting the sludge as a mixture of growing media for red shoots. The aim of this study was to determine the ability of red shoot plants to provide sludge for IPAL for the leather tanning industry and to determine the concentration that could be used as a mixture of growing media for red shoots. Variations in the composition of sludge:soil, namely 5%: 95%, 10%: 90%, 15%: 85%, 20%: 80%, 0%: 100%. This research lasted for 3 weeks with observations every 3 days of the height and diameter of the stem. The results showed that Syzygium oleana could survive from the beginning to the end of the study by giving the appropriate sludge concentration because the nutrient content was high so that it affected plant fertility both in height growth and increased plant diameter development compared to control plants. The concentration of sludge that can be used as a mixture of growing media for red shoots is below 50%. Keywords: Leather Tanning Industry, Sludge IPAL, Syzygium oleana